The field of sport-entertainment: musings about its implications and characteristics (Impetus, 2021)
In the complex field of contemporary industries of culture, communication and entertainment, few recreational areas today have so much push and impact within the civilization of entertainment and at the same time they are so ambiguous, profitable, instrumentally valuable and influential in socio-cultural, economic and political terms, such as the sports sector.